EKSTRAKSI DAN UJI STABILITAS ZAT WARNA DAUN JAMBU BIJI (Psidium guajava L.) - Lasria Pardede; Endang Kusdiyantini; Anto Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Guava leaves is known as a traditional medicine to treat various diseases, such as diarrhea, dengue fever, etc. Along with the development of technology, guava leafs is now used as a color contributor on textiles. This study aims to extract on the solvent distilled water and ethanol and to test the stability of guava leaf color pigment against the influence of storage temperature, time span of the addition of an oxidant and pH. Leaves extracted by soaked for 24 hours in distilled water solvent that has been preheated to 30°C, 50ºC, 70º C and 90ºC and ethanol with a concentration of 20%, 40%, 60%, 80% and 96%. Absorbance measurements of guava leaf extract is using spectrophotometer at a wavelength of 525 nm. The results showed that guava leaf extract has the optimum absorbance value on distilled water solvent at 90ºC and 20%ethanol. Stability test is done by storage temperature effect, oxidizing agents adding, and pH treatment. Stability test of guava leaf extract showed that extracted guava leaf color pigment is stable on 9°C storage temperature, short time oxidant adding (3 hours), and resistant to alkaline pH conditions (pH 9).Keywords: Psidium guajava L., ethanol, distilled water, spectrophotometry